Land Use Law in the Face of a Rapid-Growth Crisis: The Case of Mass-Immigration to Israel in the 1990s - Rachelle Alterman (Washington University Journal of Law & Policy, 2000)
The purpose of this Essay is to investigate the effect of an extremely accelerated growth rate—a crisis—on land use legislation and decision-making structure.
Keywords: Aliens; Land use; Regional planning